Hubungan Pola Asuh Orang Tua dengan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Kajhu Kecamatan Baitussalam Kabupaten Aceh Besar - Auliadi Saputra; Syukriadi Syukriadi; Mansuriza Mansuriza; Rawi Juwanda (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The stunting rate of Acehnese toddlers ranks 31st out of 34 provinces in Indonesia at 37, 3 percent. This number indicates that stunting is one of the public health problems in Aceh and become a threat to future generations. This study aims to see the correlation between parenting and stunting incidences of toddlers in Kajhu Public Health Center, Baitussalam, Aceh Besar. This study was a descriptive-analytical study with a cross-sectional design. The interview and questionnaire were used as data collection instruments. The population was mothers with toddlers in Kajhu Public Health Center involving 77 respondents. The sample was determined by non-probability sampling, namely a total sampling technique. The sample was 77 respondents chosen by a Total Sampling technique. This study was done in March 2024 using the Chi-Square Test ( =95%). The result of univariate analysis shows that toddlers with stunting (59, 7%), exlusive breastfeeding (42, 9%), and complementary feeding (36, 4). Further, the result of the bivariate analysis reveals there is a correlation beetwen exclusive breastfeeding (p=0,035), and complementary feeding (P 0,052), towards the stunting incidences of toddlers in Kajhu Public Health Center, Baitussalam, Aceh Besar, 2024. This study recommends that the healthworkers improve the services of Posyandu for infants and toddlers, espicially thise with body weight problems and height to prevent malnutrition and stunting problens.